3D‐Printed Bionic Solar Evaporator. Issue 7 (22nd March 2022) - Wang, Zhaolong; Zhan, Ziheng; Chen, Lei; Duan, Guihui; Cheng, Ping; Kong, Hui; Chen, Yongping; Duan, Huigao
Abstract : Solar water evaporation, which can be utilized for seawater desalination and wastewater treatment, promises freshwater security with renewable energy. Herein, a bionic solar evaporator consisting of a hydrogel solar absorber and bionic microchannels fabricated by the projection microstereolithography based 3D printing technique is proposed. Such a bioinspired solar evaporator achieves a fast water self‐transport speed and a high solar water evaporation rate of 4.12 kg·m −2 ·h −1 under 1 sun irradiation (1 kW·m −2 ), and the solar thermal efficiency can be as high as 92.1%. However, both the evaporation rate and solar thermal efficiency are greatly affected by properties of the hydrogel, geometric parameters of microchannels, and intensity of the light source. Most significantly, the bionic solar evaporator is applied for wastewater treatment including the purification of organic dyes, acid and alkali, as well as metal ions. The purification rate can be as high as 99.999%, demonstrating amazing performance for clean water production. The bioinspired water evaporator promises applications for solar energy harvesting, photothermal conversion, as well as environmental engineering, such as solar vapor generation, thermophotovoltaic cell, sewage disposal, and desalination of seawater. Abstract : Inspired by the evaporation process of the tree in nature, the bionic solar evaporator consisting of a hydrogel solar absorber and bionic microchannels, achieves a fast water self‐transport speed and a high solar water evaporation rate, which can be applied for wastewater treatment with a high purification rate up to 99.999% and a solar thermal efficiency as high as 92.1%.